2021
DOI: 10.1016/s2666-5247(20)30224-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of intestinal multidrug-resistant bacteria colonisation contracted by visitors to a high-endemic setting: a prospective, daily, real-time sampling study

Abstract: Summary Background Antimicrobial resistance is highly prevalent in low-income and middle-income countries. International travel contributes substantially to the global spread of intestinal multidrug-resistant Gram-negative bacteria. Hundreds of millions of annual visitors to low-income and middle-income countries are all exposed to intestinal multidrug-resistant Gram-negative bacteria resulting in 30–70% of them being colonised at their return. The colonisation process in high-exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(91 citation statements)
references
References 30 publications
4
75
0
1
Order By: Relevance
“…3), which highlights that ESBL carriage in veal farms is a highly dynamic process. These data extend similar observations from our group and others on ESBL clones colonizing the human microbiota, for instance where multiple transient colonizations by up to seven E. coli clones was also found to drive the intestinal carriage of bla CTX-M genes over a 22-days period (66) in humans visiting high-risk areas for acquiring ESBL-producers (67). Such similar data on intestinal dynamics in ESBL colonization is noticeable considering the differences in gut microbiota composition between humans and cattle at inter-species level (6870) and intra-species level (71, 72).…”
Section: Discussionsupporting
confidence: 90%
“…3), which highlights that ESBL carriage in veal farms is a highly dynamic process. These data extend similar observations from our group and others on ESBL clones colonizing the human microbiota, for instance where multiple transient colonizations by up to seven E. coli clones was also found to drive the intestinal carriage of bla CTX-M genes over a 22-days period (66) in humans visiting high-risk areas for acquiring ESBL-producers (67). Such similar data on intestinal dynamics in ESBL colonization is noticeable considering the differences in gut microbiota composition between humans and cattle at inter-species level (6870) and intra-species level (71, 72).…”
Section: Discussionsupporting
confidence: 90%
“…Antimicrobial usage, travelers’ diarrhea and destination have been repeatedly identified as risk factors for AMR bacterial acquisition during travel (Fig. 1 ) [ 22 ▪ , 26 , 29 ▪ , 37 ▪▪ , 41 ▪▪ , 45 ▪ ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…A study of 20 European travelers to Laos in 2015 found that 70% of participants were colonized at the end of the study. All participants had at least transiently acquired ESBL-PE, the majority of which were E. coli , and 28% of isolates had plasmid-mediated colistin resistance [ 45 ▪ ]. Further evidence suggests that travel to Africa (other than Southern Africa) and South Asia increased risk of CTX-M group 1 acquisition; there appears to be a regional association with specific CTX genes encoding ESBL's [ 29 ▪ ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Im Vordergrund stehen dabei Enterobakterien, die durch den Erwerb und die Verbreitung von Beta-Laktamasen mit erweitertem Spektrum ("extended spectrum betalactamase", ESBL), die Resistenzen gegen die meisten Betalaktam-Antibiotika verleihen, zunehmend unempfindlich gegen Erstlinien-Antibiotika geworden sind [19]. Eine rezente Echtzeitcharakterisierung der Dynamik der Besiedlung mit MRGN während der Reise deutet auf sequenzielle vorübergehende Kolonisationsereignisse hin, die eine ständige mikrobielle Konkurrenz beinhaltet und nahelegt, dass Reisende einer größeren Belastung durch MRGN ausgesetzt sind als bislang angenommen [20]. Diese Daten unterstreichen die Notwendigkeit, einer Reisediarrhö vorzubeugen und den Einsatz von Antibiotika zu begrenzen, wodurch die beiden Hauptfaktoren, die für eine intestinale MRGN-Kolonisation prädisponieren, adressiert werden.…”
Section: Risikoeinschätzung Hinsichtlich Des Erwerbs Multiresistenter Darmbakterienunclassified